A review of recent advances in nanodiamond-mediated drug delivery in cancer. (4th March 2021) - Perevedentseva, Elena; Lin, Yu-Chung; Cheng, Chia-Liang
ABSTRACT: Introduction: Nanodiamond (ND) refers to diamond particles with sizes from few to near 100 nanometers. For its superb physical, chemical and spectroscopic properties, it has been proposed and studied with the aims for bio imaging and drug delivery. Many modalities on conjugating drug molecules on ND to form ND-X for more efficient drug delivery have been demonstrated in the cellular and animal models. Area covered: Many novel drug delivery approaches utilizing nanodiamond as a platform have been demonstrated recently. This review summarizes recent developments on the nanodiamond facilitated drug delivery, from the ND-X complexes preparations to tests in the cellular and animal models. The outlook on clinical translation is discussed. Expert opinion: Nanodiamond and drug complexes (ND-X) produced from different methods are realized for drug delivery; almost all studies reported ND-X being more efficient compared to pure drug alone. However, ND of particle size less than 10 nm are found more toxic due to size and surface structure, and strongly aggregate. In vivo studies demonstrate ND accumulation in animal organs and no confirmed long-term effect studies on their release from organs are available. Standardized nanodiamond materials and drug delivery approaches are needed to advance the applications to the clinical level.